Functional Outcomes of Arthroscopic Bankart Repair in Indian Population: A Systematic Review and a Meta-analysis - Kalia, R. B.; Arora, Manit; Paul, Souvik; Chitten, Jojin Jose (Journal of arthroscopy and joint surgery, 2024)
Abstract Introduction: The past two decades have witnessed significant development in arthroscopic management for recurrent anterior shoulder instability. Currently, arthroscopic Bankart repair (ABR) is popular in the treatment of anterior shoulder instability. There is a dramatic rise in the number of orthopedic surgeons in India specializing in shoulder surgery and is believed to be secondary to the advancement in arthroscopic techniques and implants. However, there is a paucity of Indian literature on functional outcomes of ABR. The purpose of the current review is to better understand the functional outcomes of ABR in the Indian population. Methods: A search of major databases (Embase, Ovid Medline, Google Scholar, and Cochrane Library) was performed in April 2020. Reference lists of selected research articles were further screened in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Inclusion and exclusion criteria for analysis were used to generate the final list of studies. Results: A total of ten research studies were included in the final analysis representing a pooled patient population set of 391 patients. The mean age for patients across the studies was 27 years (range: 24-29) of age and the average number of dislocations before surgery was five (range: 0-14). The average follow-up period post-surgery was 20 months (range: 6-27 months). Among the functional scores, the average UCLA score improved from 22 (range: 18-30) at preoperatively to 32 (range: 31-35), and the mean Rowe score improved from an average of 27 (range: 24-63) preoperatively to 91 (range: 90-94) during the follow up duration. The average postoperative re-dislocation rate was 7% (range: 0%-10%). Conclusion: In the Indian population, ABR provides consistently good functional outcomes with a low postoperative re-dislocation rate, which is at par with the global data. Further studies with larger sample sizes and longer follow-ups are needed to validate these results.